Large-scale rapid detection of circulating microRNAs in plasma for diagnosis and screening of specific diseases. Issue 36 (4th September 2019) - Ding, Han; An, Yi; Zhao, Tao; Liu, Bing; Wang, Yin; Zhang, Lei; Wang, Yu; Zhang, Yuan; Wang, Man; Dong, Yanhan; Hu, Longgang; Zhao, Bu-Chang; et al.
Abstract : miRNAs may serve as new biomarkers that can be used for disease diagnosis. This study will contribute to the development of a universal, large-scale technology for direct in situ detection of miRNAs in patients with heart diseases. Abstract : microRNAs are a type of evolutionarily conserved small non-coding RNA with a length of 18–25 nucleotides. In recent years, increasing studies have shown that the content of specific miRNAs in the blood changes significantly during the occurrence and development of major diseases such as cardiovascular disease and cancer. Therefore, miRNAs may serve as important new biomarkers that can be used for disease diagnosis in the future. Here, we improved the polyethylene glycol layer on the surface of a traditional silicon sphere to specifically capture miRNAs by means of a full-function microplate detector, at 100 microliters. The detection limit for specific miRNAs per liter of plasma can reach 1 fM, and simultaneous detection of 96 samples can be achieved. Compared with the traditional real-time PCR technology, our detection eliminates the complex steps of miRNA extraction, reverse transcription, amplification, etc . and avoids more human error in the detection process. Using the full-featured microwell detector, we can rapidly detect specific miRNAs in plasma, which can be used in the diagnosis of cardiovascular diseases in the future.